Managing the design process : implementing design : an essential manual for the working designer - Stone, Terry Lee. (Beverly, Mass. : Rockport Publishers, 2010)
This title focuses on design implementation and execution. This is where design ideas become real, tangible goods in the marketplace and beyond. This book examines design management concepts and methods in real world applications.
Includes bibliographical references (p. 206) and index.
Keywords: Commercial art -- Management; Design services -- Management